Overview of Dietary Compliance in Hypertensive Patients at Haji Adam Malik Hospital Medan in 2022 - Sigalingging, Vina Yolanda Sari; Pakpahan, Rotua Elvina; Gea, Wilda Satriana (Sean Institute, 2022)
High blood pressure is an abnormal increase in blood pressure in the arteries over a period of time. According to WHO, the normal limit for blood pressure is 140/90 mmHg, while a person is declared to have hypertension if his blood pressure is >160/95 mmHg. One of the factors that can affect controllable blood pressure is lifestyle or lifestyle, including the application of diet. The purpose of this study is to determine the description of diet compliance in hypertensive patients at Haji Adam Malik General Hospital Medan 2022. This study uses a descriptive method. Sampling technique using purposive sampling with a sample of 39 respondents. The measuring instrument uses is a questionnaire. The results of this study show that the category of adherence to the hypertension diet is (97.4%), and the category of non-adherence to the hypertension diet is (2.6%). It is expected that people with hypertension will maintain and improve their diet compliance better, reduce consumption of drinks and foods with high blood pressure.